2021
DOI: 10.1177/01939459211021625
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health, Behavior Change Skills, and Eating Behaviors in Postpartum Women

Abstract: Excessive postpartum weight retention conveys risks for future metabolic diseases. Eating behaviors influence postpartum weight retention; however, the modifiable predictors of eating behaviors remain unclear. Using data from a three-arm, randomized controlled trial, the purpose of this study was to examine the longitudinal associations of mental health (e.g., depressive symptoms) and behavior change skills (e.g., self-efficacy) with eating behaviors (i.e., compensatory restraint, routine restraint, emotional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…An American study found that women’s eating behavior did not change significantly during the first 6–18 months following childbirth [ 16 ], although some researchers have speculated that postpartum eating behavior may impact mental health [ 14 ]. In the present study, we extended the scope to investigate the relationship between pre-existing eating patterns, food intake behavior, and psychological depression [ 14 , 32 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An American study found that women’s eating behavior did not change significantly during the first 6–18 months following childbirth [ 16 ], although some researchers have speculated that postpartum eating behavior may impact mental health [ 14 ]. In the present study, we extended the scope to investigate the relationship between pre-existing eating patterns, food intake behavior, and psychological depression [ 14 , 32 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Yu et al (2022). found that emotional overeating and other unhealthy eating behaviors were positively associated with postpartum depression (PPD) in women 6–18 months after childbirth [ 16 ]. Research has also indicated concerning links between early postpartum eating habits, such as emotion-driven eating and problematic eating attitudes requiring psychiatric attention, and PPD [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prenatal stress has been linked to the initiation of various physical and mental health issues in women, including inadequate nutrition, heightened risk of cardiovascular diseases, elevated anxiety levels and postpartum depression 15. Postpartum stress may lead to postpartum depression and postpartum weight retention due to abnormal eating behaviours 16. Studies have confirmed that depression is associated with an elevated risk of cardiovascular disease,17 18 while postpartum weight retention is associated with later adverse cardiovascular health 19…”
Section: Introductionmentioning
confidence: 99%
“…These women are at increased risk for excessive gestational weight gain (GWG) 3 and therefore postpartum weight retention (PPWR) 4 . Globally, 50% to 75% of women are not returning to pre‐pregnancy weight 12 months after childbirth, 5,6 and this may lead to long‐term weight retention and associated cardiovascular and metabolic risks 5,7 . Body composition (i.e., fat‐ and muscle mass, visceral fat) is a strong marker for women's global metabolic health, but data on the evolution of maternal body composition after childbirth are scarce 4 …”
Section: Introductionmentioning
confidence: 99%
“…4 Globally, 50% to 75% of women are not returning to pre-pregnancy weight 12 months after childbirth, 5,6 and this may lead to long-term weight retention and associated cardiovascular and metabolic risks. 5,7 Body composition (i.e., fat-and muscle mass, visceral fat) is a strong marker for women's global metabolic health, but data on the evolution of maternal body composition after childbirth are scarce. 4 Women with pre-pregnancy overweight or obesity, whether or not in combination with excessive GWG, are at increased risk for postpartum depressive symptoms compared to their counterparts with a normal weight at the start of pregnancy.…”
Section: Introductionmentioning
confidence: 99%